Synthesis of gem -difluoromethylenated polycyclic cage compounds - Chonticha Masusai (2018)
© 2015 American Chemical Society. The synthesis of gem-difluoromethylenated polycyclic cage compounds, utilizing PhSCF2SiMe3 as a gem-difluoromethylene building block, is described. The fluoride-catalyzed nucleophilic addition of PhSCF2SiMe3 to both maleic anhydride-cyclopentadiene and maleic anhydride-cyclohexadiene adducts was accomplished with high stereoselectivity to provide the corresponding adducts that were treated with Grignard reagents, followed by acid-catalyzed lactonization to afford the corresponding γ-butyrolactones, each as a single isomer. These γ-butyrolactones underwent intramolecular radical cyclization to give the corresponding tetracyclic cage γ-butyrolactones, which were employed as precursors for the synthesis of gem-difluoromethylenated tetracyclic cage lactols or tetracyclic cage furans, upon treatment with Grignard reagents.